Modulation of protein fate decision by small molecules: targeting molecular chaperone machinery - Lei Wang; Xiaoli Xu; Zhengyu Jiang; Qidong You (Acta Pharmaceutica Sinica B, 2020)
Modulation of protein fate decision and protein homeostasis plays a significant role in altering the protein level, which acts as an orientation to develop drugs with new mechanisms. The molecular chaperones exert significant biological functions on modulation of protein fate decision and protein homeostasis under constantly changing environmental conditions through extensive protein–protein interactions (PPIs) with their client proteins. With the help of molecular chaperone machinery, the processes of protein folding, trafficking, quality control and degradation of client proteins could be arranged properly. The core members of molecular chaperones, including heat shock proteins (HSPs) family and their co-chaperones, are emerging as potential drug targets since they are involved in numerous disease conditions. Development of small molecule modulators targeting not only chaperones themselves but also the PPIs among chaperones, co-chaperones and clients is attracting more and more attention. These modulators are widely used as chemical tools to study chaperone networks as well as potential drug candidates for a broader set of diseases. Here, we reviewed the key checkpoints of molecular chaperone machinery HSPs as well as their co-chaperones to discuss the small molecules targeting on them for modulation of protein fate decision.